A stochastic approach for upgrading Cultural Heritage framed concrete buildings by cable-ties to prevent progressive collapse under seismic sequences - Liolios , Angelos; Hatzigeorgiou , George; Liolios , Konstantinos; Peidis , Dimitrios (Technical Annals, 2022)
Old industrial reinforced concrete (RC) structures included to built Cultural Heritage are subjected sometimes to obligatory removal of some structural element-members, e.g. columns. In such cases, a modification of the structural response and a redistribution of internal actions can result to a requirement for upgrading the remaining structure after the removal of the degraded elements in order to avoid a progressive collapse. The present study deals with such a case, which concerns the stochastic computational analysis of historic framed RC structures under the removal of some columns and the so-induced requirement of a strengthening by ties (tension only elements). The unilateral behaviour of these cable-ties, which can undertake only tension, is strictly considered. The response under seismic sequences of the remaining historic RC structure strengthened by ties is computed considering uncertain-but-bounded input parameters.